2017
DOI: 10.21608/asejaiqjsae.2017.4830
|View full text |Cite
|
Sign up to set email alerts
|

Botanical oils as eco-friendly alternatives for controlling the rice weevil Sitophilus oryzae

Abstract: The rice weevil Sitophilus oryzae is a major stored grain pest infesting many grains in storage mainly wheat, rice and maize. Toxic effects of certain extracted botanical essential oils (EOs) were evaluated against the adults of Sitophilus oryzae (Linnaeus) (Coleoptera: Curculionidae). Bioassays were carried out by fumigation and guide tables were presented to show the effective range of concentrations of each of the evaluated essential oils and their corresponding mean number of responded insects. The essenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…When exposure period is extended, mortality was increased which also lower the LC50 value. It is reported that clove oil showed its higher toxicity to S. oryzae only after 72 h (Saad et al 2017). Mishra et al (2012) evaluated the fumigation effect of clove oil against S. oryzae where LC50 of 17.32 and 15.34 μl were achieved at 24 and 48 h, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…When exposure period is extended, mortality was increased which also lower the LC50 value. It is reported that clove oil showed its higher toxicity to S. oryzae only after 72 h (Saad et al 2017). Mishra et al (2012) evaluated the fumigation effect of clove oil against S. oryzae where LC50 of 17.32 and 15.34 μl were achieved at 24 and 48 h, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…These problems have stressed on the necessity for new alternatives with selective effects for the control of stored product insects. Among the available alternatives, plants-based products, such as essential oils, may offer a reliable tool for the management of stored product insects (Saad et al, 2017).…”
Section: Introductionmentioning
confidence: 99%